Peningkatan Kompetensi Mahasiswa Sistem Informasi Universitas Jambi dalam Keamanan Data Melalui Penerapan Teori Bilangan - Rarasati, Niken; Sormin, Corry; Kholijah, Gusmi; Multahadah, Cut; Alim, Khairul (Jurnal Pengembangan dan Pengabdian Masyarakat Multikultural, 2025)
The urgency of this community service activity is based on the increasing threats to data security in the digital era, which demand the preparedness of human resources who are not only skilled in application and information system development, but also possess a strong understanding of the fundamental principles of data protection. Students of the Information Systems Study Program, Universitas Jambi, as future professionals in the field of information technology, need to be equipped not only with technical programming skills but also with a fundamental understanding of cryptographic concepts. One of the main foundations of modern cryptography is number theory, which includes topics such as prime factorization, congruence, and the use of large prime numbers. However, at the undergraduate level, mastery of these concepts is still relatively low and has not been widely applied in contextual settings. This community service activity aims to improve the literacy and competence of Information Systems students in understanding and applying number theory in data security systems. Through training and mentoring, students will be introduced to basic concepts of number theory and their implementation in simple cryptographic algorithms such as RSA, Diffie–Hellman, and encryption systems based on modular operations.